2016
DOI: 10.2106/jbjs.15.00810
|View full text |Cite
|
Sign up to set email alerts
|

Combined Intra-Articular and Intravenous Tranexamic Acid Reduces Blood Loss in Total Knee Arthroplasty

Abstract: Therapeutic Level I. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
106
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(111 citation statements)
references
References 34 publications
(39 reference statements)
0
106
1
4
Order By: Relevance
“…Seven studies give a detailed description of the random sequence generation, [18,2022,24,26,27,30] and 5 trials perform the allocation concealment. [18,19,22,26,30] TXA is an anti-fibrinolytic agent, and the efficacy of TXA was tested by the total blood loss and patients’ need for transfusion. The antifibrinolytic agents have the potential to increase the occurrence of DVT; thus, the safety of TXA was measured by the occurrence of DVT.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Seven studies give a detailed description of the random sequence generation, [18,2022,24,26,27,30] and 5 trials perform the allocation concealment. [18,19,22,26,30] TXA is an anti-fibrinolytic agent, and the efficacy of TXA was tested by the total blood loss and patients’ need for transfusion. The antifibrinolytic agents have the potential to increase the occurrence of DVT; thus, the safety of TXA was measured by the occurrence of DVT.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 7 trials [2022,24,26,27,30] with 1110 patients perform the total blood loss after TKA, and 7 studies [2022,24,26,27,30] compared the combined topical TXA with intravenous TXA with control, 3 studies [19,21,28] compared the combined topical TXA with intravenous TXA with intravenous TXA, and 3 studies [18,21,24] compared the combined TXA with the topical administration TXA. The pooled meta-analysis indicated that the combined topical TXA with intravenous TXA can reduce the total blood loss compared with placebo with a mean of 458.66 mL and the difference is statistically significant (MD = −458.66, 95% CI: −655.40 to 261.91, P  < 0.001, Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that this method (combined TXA) can effectively reduce the amount of bleeding after TKA. Nevertheless, these studies reported inconsistent results of comparing combined TXA with IV or IA TXA alone on TKA [1517]. Therefore, this meta-analysis was designed to compare the effectiveness and safety of combined TXA with IV TXA or IA TXA for patients undergoing primary TKA through evaluating the total blood loss, blood volume of drainage, transfusion rate, and thromboembolic complications.…”
Section: Introductionmentioning
confidence: 99%
“…Combined intra-articular and intravenous delivery has been shown to result in a greater reduction in blood loss than intravenous delivery alone for primary TKA,55 or intra-articular delivery alone for revision TKA 56. Intra-articular delivery alone may be as efficacious as intravenous57 or combined intra-articular and intravenous delivery58 for primary TKA; however, the use of different tranexamic doses between studies limits the interpretation.…”
Section: Intraoperativementioning
confidence: 99%